Beneficiaries or Charity: The Influence of the Source of Acknowledgments - Wenting, Feng; Yuanping, Xu; Tao, Wang (Frontiers in Psychology, 2021)
This study employs entitativity theory to explore how acknowledgment letters from various thankers (e.g., a group of beneficiaries, a charity) influence donors’ subsequent donation desires. This empirical research consists of 3 experiments. Study 1 reveals that an acknowledgment letter from a group of beneficiaries elicits more favorable subsequent donation desires than an acknowledgment letter from a charity. To shed light on the psychological mechanism underlying this effect, study 2 shows that a categorical appellation can enhance the effects of an acknowledgment letter sent by a charity. Study 3 reveals that the influence of the thanker is stronger under no external pressure conditions (than under external pressure). The current study offers insightful suggestions for the management and administration of charities.